Biometals in rare neurodegenerative disorders of childhood - Parker, Sarah J.; Koistinaho, Jari; White, Anthony R.; Kanninen, Katja M. (Frontiers in Aging Neuroscience, 2013)
Copper, iron, and zinc are just three of the main biometals critical for correct functioning of the central nervous system (CNS). They have diverse roles in many functional processes including but not limited to enzyme catalysis, protein stabilization, and energy production. The range of metal concentrations within the body is tightly regulated and when the balance is perturbed, debilitating effects ensue. Homeostasis of brain biometals is mainly controlled by various metal transporters and metal sequestering proteins. The biological roles of biometals are vastly reviewed in the literature with a large focus on the connection to neurological conditions associated with ageing. Biometals are also implicated in a variety of debilitating inherited childhood disorders, some of which arise soon following birth or as the child progresses into early adulthood. This review acts to highlight what we know about biometals in childhood neurological disorders such as Wilson's disease (WD), Menkes disease (MD), neuronal ceroid lipofuscinoses (NCLs), and neurodegeneration with brain iron accumulation (NBIA). Also discussed are some of the animal models available to determine the pathological mechanisms in these childhood disorders, which we hope will aid in our understanding of the role of biometals in disease and in attaining possible therapeutics in the future.